The effect of mental training in developing the level of field intelligence of junior soccer players (Journal of the College of Basic Education, 2022)
The main objectives of the research were as follows:1. Putting practical exercises for mental training to develop the level of field intelligence for young soccer players.2. Identifying the impact of mental training exercises on developing the level of field intelligence for young soccer players.